PENGARUH COACHING LEADERSHIP DAN LINGKUNGAN KERJA TERHADAP TURNOVER KARYAWAN - Chintya Rindiani; Onsardi Onsardi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2026)
This study aims to determine the effect of Coaching Leadership and Work Environment on the Turnover Intention of Generation Z employees at Mylova, Bengkulu City. This research employed a quantitative approach, with a sample of 55 respondents consisting of Generation Z employees at Mylova, Bengkulu City. Data were collected through the distribution of questionnaires and analyzed using SPSS through instrument testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results of the t-test hypothesis for the Coaching Leadership variable showed that the t-value was greater than the t-table value (-2,498 > 2.007) and the significance value was less than α (0.01 < 0.05). The Work Environment variable showed that the t-value was also greater than the t-table value (-4,796 > 2.007) and the significance value was less than α (0.00 < 0.05). The results of the F-test showed that the F-value was 496.450, which was greater than the F-table value of 3.18, with a significance value of 0.00 < 0.05. Based on the research findings, it can be concluded that Coaching Leadership and Work Environment have both partial and simultaneous effects on the Turnover Intention of Generation Z employees at Mylova, Bengkulu City. Keywords: Coaching Leadership, Word Environment, Turnover Intention